2010
DOI: 10.1111/j.1464-410x.2010.09640.x
|View full text |Cite
|
Sign up to set email alerts
|

Superior efficacy of fesoterodine over tolterodine extended release with rapid onset: a prospective, head‐to‐head, placebo‐controlled trial

Abstract: placebo on UUI episodes (primary endpoint), micturitions, urgency and most other diary endpoints, and on the PPBC, UPS and all OAB Questionnaire scales and domains (all P < 0.05).• Superiority of fesoterodine 8 mg over tolterodine ER 4 mg was seen as early as week 4 (3 weeks after escalation to fesoterodine 8 mg). At week 1, fesoterodine 4 mg was superior to placebo on most diary variables, the PPBC and the UPS (all P < 0.05). Dry mouth and constipation rates were 28% and 4% with fesoterodine, 13% and 3% with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 23 publications
6
54
0
1
Order By: Relevance
“…The number of participants who required catheterization (n = 3, 0.8% vs n = 1, 0.3%) and the number who discontinued the study because of urinary retention (n = 4, 1.0% vs n = 1, 0.3%) were also higher with fesoterodine than placebo. The overall discontinuation rates in the fesoterodine (19.9%) and placebo (13.2%) groups in the present study were at the high end of the range of discontinuation rates observed in fesoterodine (10-21%) and placebo (9-15%) arms of trials conducted in younger participants; 18,19,34,35 discontinuation rates in the present study were slightly higher in participants older than 75 in both treatment groups.…”
Section: Discussionsupporting
confidence: 39%
“…The number of participants who required catheterization (n = 3, 0.8% vs n = 1, 0.3%) and the number who discontinued the study because of urinary retention (n = 4, 1.0% vs n = 1, 0.3%) were also higher with fesoterodine than placebo. The overall discontinuation rates in the fesoterodine (19.9%) and placebo (13.2%) groups in the present study were at the high end of the range of discontinuation rates observed in fesoterodine (10-21%) and placebo (9-15%) arms of trials conducted in younger participants; 18,19,34,35 discontinuation rates in the present study were slightly higher in participants older than 75 in both treatment groups.…”
Section: Discussionsupporting
confidence: 39%
“…Again, fesoterodine was superior to tolterodine ER in reducing mean daily UUI episodes (P00.0072), micturitions (P0 0.0016), urgency (P<0.0001), and other secondary end points. Likewise, fesoterodine had a higher incidence of dry mouth (28%, 13%, and 5% with fesoterodine, tolterodine, and placebo, respectively), although AE-related discontinuation rates were comparable [44].…”
Section: Comparative Studiesmentioning
confidence: 92%
“…Two studies have compared fesoterodine with tolterodine [43,44]. In a double-blind RCT comparing fesoterodine (4-mg dose for 1 week, then 8 mg for 11 weeks), tolterodine ER (4 mg), and placebo, fesoterodine (8 mg) significantly decreased mean daily UUI episodes after 12 weeks more than tolterodine ER (-1.72 vs -1.61; P<0.05) and placebo (-1.72 vs -1.46; P<0.005) [43].…”
Section: Comparative Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxybutynin, tolterodine, trospium, solifenacin, darifenacin and fesoterodine are muscarinic receptor antagonists commonly used in the treatment of overactive bladder, and each of these drugs blocks M3 and/or M2 receptors, which are the intended targets since the latter mediate smooth muscle relaxation in the bladder. Dry mouth is an ADR of varying severity depending on the drug; for example, tolterodine appears to produces less dry mouth than fesoterodine although each drug interacts with a number of muscarinic receptors including M3 ( [ 53 ], [ 54 ], [ 55 ], [ 56 ]). Studies on the mouse have compared some prescribed anticholinergics used in the treatment of overactive bladders -oxybutynin, solifenacin and tolterodine.…”
Section: Efferent Signalling and Muscarinic Receptor Antagonistsmentioning
confidence: 99%